Thematic Exegesis Analysis of Religious Polarization on Social Media - Ahmad Mahfud; Zulfatul Wasilah (Jurnal Indonesia Studi Moderasi Beragama, 2026)
Background: Religious polarisation on social media has become a serious challenge in plural societies, marked by the proliferation of hate speech, misinformation, and exclusive religious interpretations that intensify social fragmentation. Objective: This study aims to analyse Qur’anic values as a foundation for religious communication ethics in responding to the dynamics of religious polarisation in digital spaces. Method: The research employs a qualitative approach using thematic exegesis (maudhu‘i). The data are derived from Qur’anic verses related to the principles of moderation (wasathiyah), freedom of religion, human pluralism, tabayyun (information verification), ethics of dialogue, and peaceful relations with non-Muslims. The analysis is conducted through a comparative examination of classical and contemporary exegeses to identify their contextual relevance within the social media ecosystem. Result: The findings indicate that these Qur’anic values establish a normative framework that promotes moderate, inclusive, and verification-based communication while preventing the escalation of digital conflict. Conclusion: The Qur’an serves as a comprehensive ethical guide to reducing religious polarisation in digital spaces by fostering dialogue, tolerance, and responsibility. Contribution: This study enriches contextual exegesis in the digital era and offers a Qur’an-based framework for the ethics of religious communication to address religious polarisation on social media.